Small acts to make safe space: a case study of the Queer Liberation Library as a queer space - Coltman, Z. (Information Research an international electronic journal, 2025)
Introduction. This paper examines small acts from the Queer Liberation Library (QLL) that makes it a queer space as defined in previous research. This emphasises the need for access to those with multiple minority identities, and the ways in which other libraries not focused on exclusively queer literature and membership can take these small changes to make a big impact. Method. Using QLL as a case study, this paper focuses on the creation of queer space as a heterotopic mirror to normative space, refusing the unqueer spaces that attempt to enforce binaries through critical librarianship. Phenomenology is used to describe individuals’ orientations towards the normative, queer and unqueer spaces mentioned above. Analysis. The analysis takes a broad look at the purpose of QLL and other queer-focused libraries before narrowing the topic to look at three small acts on QLL’s part that build the queer space of this library: the quick exit function on their website, the lists and collections they curate monthly and QLL’s policies (collection management and membership). Conclusions. Though there is much that could, and should, be done to build queer space into public libraries, especially for multi-minority individuals, this paper argues that small acts can and should be implemented before tackling larger tasks that require excess manpower, funding and time. Though these small acts do not replace the need for larger change, they can be implemented quickly and work to make public libraries safe spaces while larger changes are slowly implemented.